Public Security and Order in the Qur'anic Perspective and its Implications for the Duties of the Indonesian National Police (POLRI) - Asep Amar Permana; Eni Zulaiha (UIN Sunan Gunung Djati Bandung, 2026)
Public security and order are essential foundations of social and state life. In the Qur’anic perspective, security (amān) is not limited to physical protection but also includes social peace, justice, and public welfare. The Indonesian National Police (Polri) holds a strategic role in translating these values into concrete practices of law enforcement and national security. This study examines the Qur’anic concept of public security and order and analyzes its implications for Polri’s duties within the modern Indonesian state. Using a qualitative-normative approach, the research applies textual analysis of relevant Qur’anic verses and compares them with Polri’s regulations, roles, and institutional mandates, supported by academic literature on religion, law, and policing. The findings show a strong alignment between Polri’s responsibilities and Qur’anic principles, particularly in upholding justice, protecting fundamental human rights, prioritizing social harmony, and maintaining order through a humanistic approach. Integrating Qur’anic values into Polri’s operations can enhance institutional legitimacy, strengthen professionalism, and promote sustainable security in the face of contemporary challenges.